Üniversite Öğrencilerinde Dinin Etkisi ile Tüketici Karar Verme Tarzları Arasındaki İlişki - (:unkn) unknown (My University, 2017)
Küreselleşme ve artan rekabet ortamında tüketici davranışlarının belirlenmesine yönelik birçok sınıflandırma çalışmaları yapılmaktadır. Dinsel etkilerde sadece kişilerin dini yaşam alanlarını değil aynı zamanda din dışı başka davranışlarını biçimlendirdiği için tüketici karar verme süreçlerinde etkisinin araştırılması oldukça önemli bir konudur. Bu çalışmanın amacı gençlerin dinsel etkileri hissetme düzeyleri ile tüketim tarzları arasındaki ilişkiyi incelemektir. Bu bağlamda Tüketici Karar Verme Tarzları ve Gençlerin Dinsel Etkiyi Hissetme Düzeyleri ölçekleri kullanılarak İstanbul ve Tokat'da yaşayan gençlerin katılımıyla bir anket araştırması yürütülmüştür. Elde edilen veriler ile yüzde ve frekans hesapları, ilişkisiz grup t testleri, pearson çarpım moment korelasyonu, regresyon analizleri yapılmıştır. Araştırma sonuçları ve sınırlılıkları tartışılmıştır

Various studies are being conducted regarding the determination of consumer behaviour in the era of globalization and increasing competition. Since religious influences not only structure the individuals’ religious life settings, but also their behaviours other than religion, it is important to investigate religion’s impact on consumer decision-making processes. The aim of this research is to analyse the relationship between the levels of young people’s religious influences and consumer styles. In this regard, by using Consumer Styles Inventory and The Levels of Young People’s Feeling Religious Effects as scales, a survey has been applied with the participation of young people at Istanbul and Tokat. With the data received, the calculations of percentage and frequency, independent group t tests, Pearson Moment Correlation, regression analysis have been conducted. Lastly, the results and the restrictions of the research have been discussed
The Relationship Between the Influence of Religion and Decision Making Styles of Consumers Among University Students